1992
DOI: 10.1002/gps.930070904
|View full text |Cite
|
Sign up to set email alerts
|

Primary or depressive dementia: Clinical features

Abstract: SUMMARYIn 1979, Wells tabled a list of 'major clinical features' which he found most useful in distinguishing dementia due to organic disease from dementia occurring in the context of psychiatric conditions like depression. This article reviews recent findings on the most commonly accepted items of this list and, for several of them, concludes that the evidence is controversial. Newer aspects are then briefly considered which, when validated in longitudinal studies, may add to the clinician's range of implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Accurate differentiation of depression from dementia can be extremely challenging even for experienced clinicians (Mulley, 1986;Lishman, 1987;Desrosiers, 1992). This is not surprising as depression in the elderly is frequently accompanied by impaired cognition or 'pseudodementia' (Jorm, 1986), whereas up to 60% of patients with Alzheimer's disease (AD) show some depressive symptoms (Burns el al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate differentiation of depression from dementia can be extremely challenging even for experienced clinicians (Mulley, 1986;Lishman, 1987;Desrosiers, 1992). This is not surprising as depression in the elderly is frequently accompanied by impaired cognition or 'pseudodementia' (Jorm, 1986), whereas up to 60% of patients with Alzheimer's disease (AD) show some depressive symptoms (Burns el al.…”
Section: Introductionmentioning
confidence: 99%
“…Wells (1979) proposed a number of clinical features that may be helpful in differentiating pseudodementia from dementia. However, few have been prospectively validated and the reliance that can be placed on these has been questioned (Desrosiers, 1992). The availability of a biological or radiological marker which could assist with differential diagnosis would be a major advance.…”
Section: Introductionmentioning
confidence: 99%
“…This leaves the third controversial issue (measurable versus unmeasurable cognitive problems) unresolved, resulting in the term`pseudodementia' encompassing two categories of patients (Ballard et al, 1996). The ®rst group was those who often have subjective memory complaints without true intellectual de®cits and give`I don't know' responses during cognitive assessment (eg Wells 1979;Desrosiers, 1992). The second group comprised those who make eorts to participate in cognitive testing but despite this show performance de®cits during cognitive assessments (eg Folstein and McHugh, 1978;Massman et al, 1992).…”
mentioning
confidence: 99%
“…Wells' proposed discriminating features suggested that some attributes (eg personal vs instrumental competence, complaint vs performance) might provide valuable pointers of the conditions whereas others (eg history of depression) remain more controversial. The greatest obstacle at this stage is that practically none of the proposed discriminating features in the literature has been validated through prospective studies (Desrosiers, 1992).…”
mentioning
confidence: 99%
“…Partly responsible for this confusion are the current difficulties in defining the concept of ‘primary dementia’ in its earliest stage.4 With no antemortem biological marker for Alzheimer's disease (AD), we must still fall back on behavioral (e.g., memory decline) and operational (e.g., symptom threshold) concepts to detect the earliest features of dementia associated with AD 5–7 . Thus, ambiguities arise in relation to ‘non‐harbinger’ concepts of cognitive attenuation such as ‘benign senescent forgetfulness’ or ‘age‐associated memory impairment’ 8–11 .…”
mentioning
confidence: 99%